A study of the adoption and utilization of seven collaboration technologies in large organizations in Australia and New Zealand - Pervan, Graham; Bajwa, D.; Lewis, L. (Ivy League Publishing, 2005)
This paper empirically assesses the patterns of adoption and utilization of seven CIT clusters in supporting task-oriented collaboration in organizations in Australia and New Zealand. Analysis of data collected from one hundred and fifty-six organizations indicates that these patterns vary considerable among different CITs. Furthermore, an investigation into the antecedents of adoption and utilization of CITs indicates that promotion of collaboration, decision making pattern, and IT function size are significant predictors of aggregate adoption status of CITs. While promotion of collaboration and decision making patterns also influence aggregate adoption levels of CITs, only promotion of collaboration was found to be a significant predictor of aggregate utilization level of CITs. Organizations size did not influence any aspects of CIT adoption and utilization.